Management by properties of surfaces of friction at running-in of discrete coverages in the conditions of fretting-wearness - Цыбанев, Г.В.; Марчук, В.Е.; Калиниченко, В.И. (Problems of Tribology, 2014)
Influence of geometrical parameters of small holes of discrete coverage on tribotechnical characteristics in the conditions of fretting-wearness in the period of running-in is investigated. Three running-in characteristic periods at which the friction coefficient at the level of number of weighting cycles increase has an unmonotonous character. Small hole space of discrete coverage provid an effective heat removal from the surface of tribocontact, that results the decline of the tensely-deformed state Application of discrete coverages allows to manage a processes in tribocontact during a running-in by influence on the processes of friction and wear.